Projeto do Trabalho de Microempresa de Confecções em João Pessoa - Paraíba - Cavalcanti, Ana Paula Bezerra (2020)
The textile and clothing sector has been growing in Brazil, currently the country gathers more than 33 thousand companies, 80% of which are small companies. Many of these companies are based on the family management model, in which there are little planning, and several organizational problems. For the function of the seamstress, the ergonomic demand is high due to long periods in the sitting posture, performing repetitive short cycle movements. Given this situation, this sector has a high rate of absence from work, being the most frequent symptoms in the upper limbs and in the spine region. In this perspective, the present study aims to carry out an analysis of the work of the seamstresses of a micro clothing company in João Pessoa - Paraíba, from an ergonomic point of view, to propose solutions to the risks evidenced in the working conditions. For this purpose, as a methodological procedure was used the steps provided for in the NR 17 application manual. In addition, tools such as flowchart, map flowchart, two-handed graph, and EWA (Ergonomics Workplace Analysis) were used, in order to measure the variables and analyze the data for the composition of this research. Hereupon, through the analysis of the seamstresses' workstation, it was possible to propose improvements in the physical, cognitive and organizational scope, such as, for example, the proposal to relay the workstation, adopt work intervals, implement a planning management and production control, to reduce overloads caused by variation in demand, among others.